El cuerpo como terreno donde el significado se inscribe y reconstruye - Pilar Díez del Corral (Arteterapia)
A didactic artistic unit is presented in which the body is the basis where meaning is registered and built. It is established as a project designed to articulate the difference of a form of education intended for inclusion. To develop this proposal we modified the official didactic unit, based on the development of the ability to represent human figure. The new proposal offered a new and different way within the artistic education curriculum, since it introduces the problem of the body as the basis of social meaning. The didactic unit is presented together with its planning and a chronogram in which the main phases of the project are described: the ability to visualize the complexity of body realities, reflexive closeness to the body as the basis of meaning, Representation of the personal and social body ideal, body recreation as the inclusion place. Images are shown, both of the materials offered as well as of student’s works. Some reflexions from students and a conclusion of the process are included.